Urgensi Perlindungan Hukum Bagi Whistleblower: Studi Perbandingan Indonesia-Amerika Serikat - Warna Bela Natasia; I Ketut Suyoga Arya Saputra; Waldo Christian Marpaung; Haniva Salsabilla; Bintani Putri Nusantara; Fajar Ramadhan (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The dialectics and discourse about whistleblowers in Indonesia are not active when discussing and studying the concept of justice collaborators against a large-scale crime. The glory of the whistleblower concept is not as detailed as the setting of Justice Collaborators. So, information about what and how the whistleblower mechanisms work is still covered by the black cloud in order to uncover large-scale crimes. The purpose of writing this article is to know and analyse the legal protection system against a whistleblower reporting a crime. The research method used is a normative juridical research method using conceptual approaches, legal approaches, and comparative approaches to the United States. The result of this study is that a person identified as a whistleblower, if referring to settings and comparisons, will still raise doubts caused by the uncertainty of benefits and protection for himself and his family. The conclusion of this study is that the legal protection and protection of future guarantees for someone who has been designated as a whistleblower are still very minimal. Thus, the disclosure of a large-scale criminal case becomes very difficult and focuses only on the interests of justice collaborators. Keywords: evidence; legal protection; whistleblower